The evaluation of potential immunotoxicity induced by environmental pollutant ammonia in broilers. (9th April 2019) - An, Yang; Xing, Houjuan; Zhang, Yu; Jia, Pengcheng; Gu, Xianhong; Teng, Xiaohua
ABSTRACT: Ammonia (NH3 ) is a harmful gas with irritating odor, and higher NH3 concentration was found in intensive poultry houses. Although the toxicity of NH3 is well known, little attention has been given to the mechanism of NH3 poisoning in chicken immune organs. To investigate NH3 -caused inflammatory damage of broiler spleens, in this study, a broiler model for NH3 poisoning was established, and 3 levels (including microRNA [miRNA], mRNA, and protein) were performed using qRT-PCR and western blot. The results indicated that NH3 exposure caused inflammatory damage using microstructure observation; decreased 2 inflammation-related miRNAs (miR-133a and miR-6615), 2 cytokines secreted by T helper cells 1 (Th1), and heme oxygenase-1 (HO-1); and increased 2 target genes (LOC101747543 and mothers against decapentaplegic homolog 7 [SMAD7]) of the 2 miRNAs, 7 inflammation-related factors, 3 cytokines secreted by Th2, and 5 heat shock proteins (HSPs) in broiler spleens. Our study suggested that Th1/Th2 imbalance, nuclear factor-κB (NF-κB) pathway, and compensatory response of HSPs were involved in NH3 -caused inflammatory damage in broiler spleens; there was immunotoxic effect in excess NH3 on broilers. For the first time, we discovered miR-6615 and LOC101747543 may be involved in the mechanism of broiler spleen inflammatory damage caused by NH3 via the NF-κB pathway, and further mechanism needs to be investigated. This study provides new insights for NH3 toxicity identification and risk assessment in animal husbandry production practice.